Increased Sensitivity of Mice Lacking Extrasynaptic δ-Containing GABAA Receptors to Histamine Receptor 3 Antagonists - Abdurakhmanova, Shamsiiat; Grotell, Milo; Kauhanen, Jenna; Linden, Anni-Maija; Korpi, Esa R.; Panula, Pertti (Frontiers in Pharmacology, 2020)
Histamine/GABA neurons of posterior hypothalamus send wide projections to many brain areas and participate in stabilizing the wake state. Recent research has suggested that GABA released from the histamine/GABA neurons acts on extrasynaptic GABAA receptors and balances the excitatory effect of histamine. In the current study we show the presence of vesicular GABA transporter mRNA in a majority of quantified hypothalamic histaminergic neurons, which suggest vesicular release of GABA. As histamine/GABA neurons form conventional synapses infrequently, it is possible that GABA released from these neurons diffuses to target areas by volume transmission and acts on extrasynaptic GABA receptors. To investigate this hypothesis mice lacking extrasynaptic GABAA receptor δ subunit (Gabrd KO) were used. A pharmacological approach was employed to activate histamine/GABA neurons and induce histamine and presumably, GABA, release. Control and Gabrd KO mice were treated with Hrh3 inverse agonists ciproxifan and pitolisant, which block Hrh3 autoreceptors on histamine/GABA neurons and histamine-dependently promote wakefulness. Low doses of ciproxifan (1 mg/kg) and pitolisant (5 mg/kg) affected locomotion of Gabrd KO, but not WT mice. EEG recording showed that Gabrd KO mice were also more sensitive to the wake-promoting effect of ciproxifan (3 mg/kg) than control mice. Low frequency delta waves, associated with NREM sleep, were significantly suppressed in Gabrd KO mice compared with the WT group. Ciproxifan-induced wakefulness was blocked by histamine synthesis inhibitor alpha-fluoromethylhistidine (αFMH). The findings indicate that both histamine and GABA, released from histamine/GABA neurons are involved in regulation of brain arousal states and δ subunit GABAA receptors are involved in mediating GABA response.